2021
DOI: 10.48550/arxiv.2109.02424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Building better spin models for merging binary black holes: Evidence for non-spinning and rapidly spinning nearly aligned sub-populations

Shanika Galaudage,
Colm Talbot,
Tushar Nagar
et al.

Abstract: Recent work paints a conflicting portrait of the distribution of black hole spins in merging binaries measured with gravitational waves. Some analyses find that a significant fraction of merging binaries contain at least one black hole with a spin tilt > 90 • with respect to the orbital angular momentum vector, which has been interpreted as a signature for dynamical assembly. Other analyses find the data are consistent with a bimodal population in which some binaries contain black holes with negligible spin wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 32 publications
(42 reference statements)
7
19
1
Order By: Relevance
“…Secondly, we show that our results agree with those presented in Roulet et al (2021) and Galaudage et al (2021) and show that there is evidence that the black hole population is consistent with two spin subpopulations, which, when combined, gives an overall preference for the distribution in Abbott et al (2021b). We highlight that the majority of events (∼ 80%) prefer a spin distribution with extremely low spin magnitudes while several show preference for larger spins.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Secondly, we show that our results agree with those presented in Roulet et al (2021) and Galaudage et al (2021) and show that there is evidence that the black hole population is consistent with two spin subpopulations, which, when combined, gives an overall preference for the distribution in Abbott et al (2021b). We highlight that the majority of events (∼ 80%) prefer a spin distribution with extremely low spin magnitudes while several show preference for larger spins.…”
Section: Introductionsupporting
confidence: 91%
“…This hints at possible sub-populations in the preferred spin distribution: one with negligible spins (EL) and one with larger spins (L). This is the same conclusion found by Roulet et al (2021) and Galaudage et al (2021). We therefore investigate these possible spin sub-populations by calculating odds ratios between models with negligible spin (ELI) and models with larger spins both nearly aligned with the orbital angular momentum (LA) and spins isotropically distributed (LI).…”
Section: Structure In the Preferred Spin Distributionsupporting
confidence: 72%
See 2 more Smart Citations
“…Further observations have expanded on these features, indicating that lighter binaries contribute significantly to the total merger rate (Abbott et al 2019a(Abbott et al , 2021c, black holes in heavier binaries tend to have larger spin magnitude Galaudage et al 2021;Hoy et al 2021), and as reported in this article the early results indicate the merger rate evolution of peaks in the mass distribution is disparate.…”
Section: Introductionmentioning
confidence: 54%